Assessing Cumulative Exposure of Northern Gannets to Offshore Wind Farms - M. Wing Goodale; Anita Milman (Wildlife Society Bulletin)
ABSTRACT Offshore wind farms are rapidly being permitted along the Atlantic Coast of the United States. Exposure of northern gannet (Morus bassanus) to multiple wind farms could affect the population because gannets are vulnerable to both displacement and collision. A critical question is whether wind‐farm siting decisions can reduce cumulative exposure of gannets. We quantified how 3 different wind‐farm siting scenarios would cumulatively expose gannets. Two independent gannet abundance data sets were used to ensure robustness of the analysis: 1) individual tracking data from birds captured in the mid‐Atlantic region of the United States from 2012–2015 and 2) relative abundance models developed by the National Oceanic and Atmospheric Administration from surveys conducted from 1978–2014 along the Atlantic Coast of the United States. Our results indicate that for initial development, projects sited close to shore and in shallow areas exposed gannets at the greatest rates; however, no siting scenario effectively avoided exposing gannets because of the birds’ broad distribution across the outer continental shelf. These findings suggest that gannets will be cumulatively exposed regardless of siting scenario and management actions should focus on efforts to minimize adverse effects at each wind farm rather than avoiding exposure through siting decisions. © 2020 The Wildlife Society.